Smart home care platforms: Where is the added value? - Frederic Vannieuwenborg; Thomas Van Auwermeulen; Jan Van Ooteghem; An Jacobs; Sofie Verbrugge; Didier Colle; Mario Pickavet (International Telecommunications Society (ITS), 2014)
Due to changes in the demographic situation of most Western European countries, interest in ICT supported care services grows fast. eCare services that foster a better care information exchange, social involvement, lifestyle monitoring services, etc., offered via smart care platforms integrated in the homes of the elderly are believed to be cost-effective and could lead to an increased quality of life of both care receiver and (in)formal care giver. Currently adoption and integration of these smart care platforms is slowed down by several barriers such as an unclear added value, a lack of regulations or a sustainable financial model. In this work the added value of smart home care platforms is identified for the several involved key-actors such as the care receiver, the (in)formal care providers and the care organizations. In a second step several go to market strategies are formulated and are supported by the quantification of the potential impact on current care processes in terms of time and financial resources. Because the gap between the current way of providing home care and providing home care supported by a fully integrated smart care platform seems too big to bridge in one effort, a migration path is provided for stepwise adoption and integration of smart care platforms in the current way of home care provisioning.
Keywords: 330; smart care platform; multi-actor analysis; value network analysis; impact quantification